ACADEMIC EDUCATION FOR PUBLIC HEALTH ACTIVITIES THROUGH THE CARIOCA ACADEMY PROGRAM (Fiep Bulletin - online, 2019)
INTRODUCTION: With the implementation of the Carioca Academy Program, the Physical Education professional isintroduced more intensively into the daily routine of public health services, adding the regular practice of physical activity to thedaily activities of Primary Care Units ). OBJECTIVE: To verify the academic training for public health performance of physicaleducation professionals in activity in the APS Units of the Municipal Health Department of Rio de Janeiro through the AcademiaCarioca Program. METHODOLOGY: The study had 77 participants of both sexes and as an instrument of data collection wasused an electronic questionnaire adapted, semi-structured and self-filling. RESULTS: Regarding the academic training for publichealth, 87% of the participants reported not having undergone any degree discipline related to the performance of the PhysicalEducation professional in public health and 90.9% said they feel unprepared to act in this scenario due to to the absence ofcontent related to the subject in its academic formation. CONCLUSION: The study showed that the academic formation ofPhysical Education professionals presented a lack of contents that would contribute to the construction of theoretical and / orpractical knowledge to perform in public health through the Academia Carioca Program.